Graphene-like monolayer InSe–X: several promising half-metallic nanosheets in spintronics. (21st March 2018) - Liu, Jun; Kang, Wei; Zhou, Ting-Yan; Ma, Chong-Geng
Abstract: Several half-metallic graphene-like nanosheets, namely halogen atom adsorbed InSe– X ( X = F, Cl, Br and I) nanosheets, are predicted by first-principles calculations. Then, their structural, electric and magnetic properties are studied in detail. The calculated negative adsorption energies of these InSe– X nanosheets ensure that they attain stable adsorption structures, which suggests that they may be prepared experimentally. The pristine InSe monolayer is a typical semi-conductor, whereas it is interesting that the X ion ( X = F, Cl, Br and I) adsorbed InSe– X nanosheets are electronically conductive. They can be promising and good candidates for applications of half-metallic 2D materials. The calculated magnetic moments of these nanosheets are close to 1.0 µ B . In the InSe–F nanosheet, there are sp 2 hybridized orbitals due to the crystal field effect, and its electroconductibility, half-metallicity and magnetic moments originate from the In and Se ions, not the F ion. However, in InSe– X ( X = Cl, Br and I) nanosheets, there are sp 3 hybridized orbitals, and their electroconductibility, half-metallicity and magnetic moments originate mainly from X ions, together partially with the In and Se ions.